Performance Study of Developed SMART EYE for Visually Impaired Person. - Anuar , Mohamed Kassim; Shukor, Ahmad Zaki (2013)
Direction is arguably the most pressing concern for visually impaired person. Nevertheless, we lack a convenient navigation system to guide a visually impaired person using point to point direction to reach desired destination independently while walking on tactile paving. Accessibility of this navigation system must be convenient and simple for visually impaired people. In order to provide an efficient and user friendly assistive tool, it is proposed to design and develop a navigation system using Radio Frequency Identification (RFID) to guide the visually impaired walking on tactile paving. Path planning algorithm will be implemented in this project to give the shortest path and direction as a navigation guide for visually impaired people. This project will directly contribute to society by making available a convenient navigation system for visually impaired people for a better lifestyle.